Legal Protection of Children Born Through Surrogacy: A Comparative Legal Analysis - Hardika, Made Chersyana Dwidiantari; Mahadewi, Kadek Julia (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study aims to examine the legal protection and recognition of children born through surrogacy by comparing the legal frameworks of three countries: Indonesia, Iran, and Australia. The objective is to analyze how each country regulates the civil status, identity, and inheritance rights of children born through assisted reproductive technologies, with a specific focus on surrogacy arrangements. The research method used in this study was normative legal research with a comparative approach. It utilizes secondary legal materials such as statutory laws, judicial decisions, and religious doctrines to assess the extent of legal certainty and child protection provided under each national legal system. The novelty in this research lies in its integrative comparative analysis of countries with differing legal traditions, Australia with its positivist legal framework, Iran with its reliance on Shi’a Islamic jurisprudence and religious fatwas, and Indonesia which currently lacks specific regulations governing surrogacy. This research also proposes the adoption of a Parentage Order mechanism in Indonesia, inspired by Australia’s legal model, to ensure the recognition of genetic parenthood without requiring adoption procedures. Based on the research, it is concluded that Indonesia presents the weakest legal protection due to the absence of specific legislation, resulting in legal uncertainty for children born through surrogacy. In contrast, Iran provides legal clarity through religious and judicial mechanisms, while Australia offers a well-regulated system grounded in the best interests of the child. The findings suggest that Indonesia urgently needs legal reform to recognize surrogacy and ensure comprehensive protection of children’s rights in accordance with international human rights standards.